2016
DOI: 10.1589/jpts.28.3145
|View full text |Cite
|
Sign up to set email alerts
|

Study on the quality of life of children with cerebral palsy

Abstract: [Purpose] This study aims to analyze the factors that affect the quality of life of children with cerebral palsy. [Subjects and Methods] The study subjects were 138 children, aged 7–12, who suffer from cerebral palsy. Factors affecting subjects’ quality of life were evaluated using the ICF-CY; quality of life was evaluated using the KIDSCREEN 52 − Health-Related Quality of Life questionnaire. Multiple regression analysis was conducted. [Results] The factors related to physical functions that affect subjects’ q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…The review emphasizes the significance of studies that are conducted to identify interventions that can optimize and analyse the overall development and social integration of children with cerebral palsy. The issues that justify the investigation of this literature review to be considered, as the limited understanding of factors that are closely related to analyse quality of life defining social, emotional, functional, behavioural aspects for children with cerebral palsy (Park et al, 2016), despite of having diverse studies till date at different part of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The review emphasizes the significance of studies that are conducted to identify interventions that can optimize and analyse the overall development and social integration of children with cerebral palsy. The issues that justify the investigation of this literature review to be considered, as the limited understanding of factors that are closely related to analyse quality of life defining social, emotional, functional, behavioural aspects for children with cerebral palsy (Park et al, 2016), despite of having diverse studies till date at different part of the world.…”
Section: Introductionmentioning
confidence: 99%
“… 24 In other pediatric populations, parental psychosocial factors have been shown to affect how parents assess and cope with their child's pain, 25 but data from children with CP are missing. In children with CP, unrelieved pain has been associated with decreased quality of life 26 , 27 and health‐related quality of life, 28 , 29 decreased social participation, 30 , 31 , 32 mental health problems, 28 , 33 sleep problems, 18 , 34 and limitations in performing normal daily activities. 18 , 34 , 35 In a recent systematic review, McKinnon 11 concluded that a majority of these associations remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Essas alterações variam de criança para criança, de acordo com a região lesada, porém as alterações mais encontradas são a espasticidade, hipotonia, comprometimento cognitivo, sensorial, visual, auditivo e o equilíbrio (Graham et al, 2016;Hidecker et al, 2018) Como consequência, há dificuldades na execução de suas atividades de vida diária e podem limitar o convívio em ambientes como a escola, que muitas vezes não estão adaptadas para crianças com dificuldades de locomoção. Além destas alterações, as crianças com PC podem apresentar consequências secundárias, tais como dificuldade de aprendizagem, distúrbios na fala, problemas ortopédicos e em casos mais graves a epilepsia (Meincke et al, 2018;Park et al, 2016;Shikako-Thomas et al, 2013).…”
Section: Introductionunclassified